PENGARUH PROFITABILITAS TERHADAP KEBIJAKAN DIVIDEN TUNAI DENGAN LIKUIDITAS SEBAGAI VARIABEL MODERASI (Studi terhadap Perusahaan manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2015 - 2018) - Mahmudah, Henny; Ratnawati, Tri (DiE: Jurnal Ilmu Ekonomi dan Manajemen, 2020)
In financial policy where the dividend policy becomes an important consideration,not only in terms of company management, but also from shareholders. Shareholderswill propose dividend distribution if the company is in profit. Growth in manufacturingcompanies that tend to be good and generate (profits) will be easier to see profitabilityaffecting the dividend payout ratio and of course with a stable dividend distribution.The purpose of this study: 1) To find out whether profitability has a positive andsignificant effect on cash dividend policy on manufacturing companies and 2) To findout the effect of liquidity that is owned, can it strengthen the relationship betweenprofitability on dividend policy on manufacturing companies. The approach taken inthis research is a quantitative approach. The sample selection method in this study ispurposive sampling, which is the sample selection method using certain criteria so thatit can get 10 samples of manufacturing companies. The analytical method used isdescriptive statistics, simple regression analysis (simple regression analysis) andmoderation regression analysis (Moderate Regression analysis) with pure moderatortest, coefficient of determination, F test and t test. The test results prove thatprofitability has a positive and significant impact on cash dividend policy onmanufacturing companies. Liquidity as a moderating variable is able to strengthen therelationship between profitability and cash dividend policies in manufacturingcompanies. The results of this study are expected to provide information to the publicand outside parties or investors to make investment decisions and can assess thefinancial performance of a company.Keyword : Profitabilitas, Kebijakan Dividen Tunai dan Likuiditas